2019
DOI: 10.1149/2.0101906jes
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Sensor Platform for Sensitive Detection of Iron (III) Ions Based on Pyrene-Substituted Poly(2,5-dithienylpyrrole)

Abstract: Conducting polymers, which have a great potential for use in many technological application areas, can be used to design new selective, sensitive, highly efficient and practical sensor platforms. Herein, a pyrene-substituted 2,5-dithienylpyrrole (TPP) has been synthesized and its conductive polymer has been coated electrochemically on the ITO electrode surface to form a new sensor platform. After electrochemical and surface characterization of conducting polymer based sensor platform, its electrochemical respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…[3,4] They are classified based on the method adopted for sensing, including optical, [5][6][7][8] electrochemical, [9,10] electrical, [11] thermometric, [12] mass sensitive, [13] magnetic [14][15][16] etc. They can also be classified based on the type of analyte into different types, including pH electrodes [17] and sensors for metal ions and determining gases, [18][19][20] as well as the mode of application into in vivo [21] and in vitro [22] sensors for process monitoring. Among these methods, electrochemical methods possess remarkable features, such as high sensitivity, short response time, low cost, simplicity of instrumentation, the possibility of miniaturization, and integration with portable devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] They are classified based on the method adopted for sensing, including optical, [5][6][7][8] electrochemical, [9,10] electrical, [11] thermometric, [12] mass sensitive, [13] magnetic [14][15][16] etc. They can also be classified based on the type of analyte into different types, including pH electrodes [17] and sensors for metal ions and determining gases, [18][19][20] as well as the mode of application into in vivo [21] and in vitro [22] sensors for process monitoring. Among these methods, electrochemical methods possess remarkable features, such as high sensitivity, short response time, low cost, simplicity of instrumentation, the possibility of miniaturization, and integration with portable devices.…”
Section: Introductionmentioning
confidence: 99%
“…They are classified based on the method adopted for sensing, including optical, [5–8] electrochemical, [9,10] electrical, [11] thermometric, [12] mass sensitive, [13] magnetic [14–16] etc. They can also be classified based on the type of analyte into different types, including pH electrodes [17] and sensors for metal ions and determining gases, [18–20] as well as the mode of application into in vivo [21] and in vitro [22] sensors for process monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the Au-BiNPs/SH-GO/GCE has a better sensitivity to the Fe(III). Compared with other previously reported sensors for Fe(III) detection ( Table 1 ) [ 44 , 45 , 46 , 47 , 48 , 49 ], the proposed sensing platform processed more sensitivity and lower limit of detection.…”
Section: Resultsmentioning
confidence: 91%
“…Ayranci and Ak have developed an iron(III)-sensitive sensor based on a pyrenesubstituted 2,5-dithienylpyrrole (TPP) conductive polymer electrochemically deposited on an ITO electrode's surface [178]. The investigation of the electrochemical response of the sensor to different metal ions in aqueous media showed the excellent potentiometric response to Fe(III) ions with a DL of 1.73 × 10 −7 M, whereas there was no significant electrochemical signal observed in other metal ion solutions, including Fe(II), Zn(II), Cu(II), Hg(II), and Cd(II).…”
Section: Detection Of Other Trace Metalsmentioning
confidence: 99%